(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to identify the level of creative thinking and self-actualization among female students at Abu Issa Faculty of Education, University of Zawia, examine the relationship between them, and determine the effect of creative thinking on self-actualization, The study adopted the descriptive-analytical method and was conducted on a sample of 138 female students using a questionnaire, The results showed that both creative thinking and self-actualization were at a moderate level, They also revealed a statistically significant positive relationship between the two variables and a significant effect of creative thinking on self-actualization.